Outbreak of Escherichia coli O157:H7 Related to Animal Contact at a Petting Zoo - Bryna Warshawsky; Iris Gutmanis; Bonnie Henry; Joanne Dow; Jim Reffle; Graham Pollett; Rafiq Ahmed; John Aldom; David Alves; Abdul Chagla; Bruce Ciebin; Faron Kolbe; et al. (Canadian Journal of Infectious Diseases)
OBJECTIVE: To determine the cause of an outbreak of Escherichia coli 0157:H7 related to animal exposures so that further transmission could be prevented.